Synthesis of Ag-Cr thin film metallic glasses with enhanced sulfide-resistance. (15th September 2020) - Jia, Peng; Huang, Ruiwen; Zhang, Suode; Wang, Engang; Yao, Jiahao
Abstract: The thin film glass forming region of the immiscible Ag-Cr binary system was explored by combinatorial sputtering. The electrochemical behavior of Ag-Cr alloy films with different Cr content in different corrosive environments containing S 2− or Cl- were investigated in comparison with those of pure silver. The Ag-Cr thin film metallic glasses (TFMG) exhibit much enhanced corrosion resistance in 0.01 M K2 S solution, comparing with that of the bulk silver, the Ag50 Cr50 TFMG exhibits much higher corrosion potential as well as two orders of magnitude lower corrosion current density. Nevertheless, no obvious improvement of the corrosion resistance can be found for the glassy films in 0.1 M NaCl solution.